Formation and fate of low-metallicity stars in TNG50. Issue 3 (16th March 2022) - Pakmor, Rüdiger; Simpson, Christine M; van de Voort, Freeke; Hernquist, Lars; van Son, Lieke; Chruślińska, Martyna; Bieri, Rebekka; de Mink, Selma E; Springel, Volker
ABSTRACT: Low-metallicity stars give rise to unique spectacular transients and are of immense interest for understanding stellar evolution. Their importance has only grown further with the recent detections of mergers of stellar mass black holes that likely originate mainly from low-metallicity progenitor systems. Moreover, the formation of low-metallicity stars is intricately linked to galaxy evolution, in particular to early enrichment and to later accretion and mixing of lower metallicity gas. Because low-metallicity stars are difficult to observe directly, cosmological simulations are crucial for understanding their formation. Here, we quantify the rates and locations of low-metallicity star formation using the high-resolution TNG50 magnetohydrodynamical cosmological simulation, and we examine where low-metallicity stars end up at z = 0. We find that 20 per cent of stars with Z_*0.1 Z_ form after z = 2, and that such stars are still forming in galaxies of all masses at z = 0 today. Moreover, most low-metallicity stars at z = 0 reside in massive galaxies. We analyse the radial distribution of low-metallicity star formation and discuss the curious case of seven galaxies in TNG50 that form stars from primordial gas even at z = 0.